A lesson on race: the Bible and the Morant Bay rebellion in the Atlantic world - Russell, Stephen C. (Histories of slavery and its global legacies, 2025)
Stephen C. Russell tells the story of the Bible's role in Jamaica's 1865 Morant Bay rebellion and the international debates about race relations then occupying the Atlantic world. With the conclusion of the American Civil War and arguments about reconstruction underway, the Morant Bay rebellion seemed to serve as a cautionary tale about race relations. Through an interdisciplinary lens, the book demonstrates how those participating in the rebellion, and those who discussed it afterward, conceptualized events that transpired in a small town in rural Jamaica as a crucial instance that laid bare universal truths about race that could be applied to America. Russell argues that biblical slogans were used to encode competing claims about race relations. Letters, sermons, newspaper editorials, and legal depositions reveal a world in the grips of racial upheaval as everyone turned their attention to Jamaica. Intimately and accessibly told, the story draws readers into the private and public lives of the rebellion's heroes and villains.